(untitled) - A ESTININGRUM, DHIAH (RETAIN : Journal of Research in English Language Teaching, 2013)
Writing is one of English skills that should be mastered by the students. It belongs to productive skill in which ones are expected to communicate their ideas with others in a written form. In a writing composition, there are some components need to be considered. This case makes writing be more complicated than other English skills. It is suggested to create meaningful activities in order to engage students in the learning process. As Tessema (2005) stated on his journal, Project-Based Task can facilitate the students’ need and interest, and also booster the students’ motivation. This study aimed to investigate the significance difference between the students who have been given Project-Based Tasks and those who have not in their writing ability. Besides that, its purpose was to find out the students’ motivation to write after the implementation of Project-Based Task. The research method was experimental quantitative study with two groups-pretest and posttest design. The population was eleventh grade of SMAN 1 Ngadirojo. The samples got from random sampling were XI IPA 3 as the experimental group and XI IPA 2 as the control group. Both groups were given writing test as the pretest and posttest. Then, the score was analyzed by using T-test. Another research instrument was motivation test which was given to the experimental group only and the result of it was presented in the form of percentage. The result of this study showed that there was significant difference between the writing score of students who have been taught by using Project-Based Task and those who have not. It was proven by the t value that higher than the t table (tvalue > t.05). The t value was 2,565 and the t table with the degree of freedom 60 (the closest to 57) was 2,000. From the motivation test result, the students mostly had higher motivation to write after the treatment given. Therefore, it can be concluded that Project-Based Task was effective to improve the eleventh graders’ writing ability and improve their motivation to write. Key Words: Writing ability, Project-Based Task, motivation Abstrak Menulis adalah salah satu kemampuan berbahasa Inggris yang seharusnya dapat dikuasai oleh siswa. Ini tergolong dalam kemampuan yang bersifat produktif dimana seseorang diharapkan untuk menyampaikan gagasannya kepada orang lain dalam secara tertulis. Dalam suatu komposisi tulisan, ada beberapa komponen yang perlu dipikirkan.Hal ini membuat menulis lebih rumit disbanding dengan kemampuan lainnya dalam bahasa Inggris. Disarankan untuk menciptakan kegiatan-kegiatan yang bermakna untuk mengajak siswa terlibat dalam proses pembelajaran. Seperti yang dikatakan oleh Tessema (2005) dalam jurnalnya bahwa Project-Based Task dapat memfasilitasi kebutuhan dan minat siswa, dan juga meningkatkan motivasi siswa. Penelitian ini bertujuan untuk meneliti perbedaan yang berarti pada kemampuan menulis siswa yang diberi Project-Based Task dan yang tidak. Selain itu, ini bertujuan untuk mengetahui motivasi siswa untuk menulis setelah penerapan Project-Based Task. Metode penelitian yang digunakan adalah kuantitatif eksperimental dengan menggunakan dua grup pretest-posttest. Populasi penelitian adalah siswa kelas sebelas SMAN 1 Ngadirojo dan sampel yang diperoleh secara acak adalah XI IPA 3 sebagai eksperimental grup dan XI IPA 2 sebagai control grup. Kedua grup tersebut diberi tes menulis sebagai pretest dan posttest. Kemudian skor dari tes dianalisa menggunakan T-test. Instrumen penelitian lainnya yaitu motivation test yang diberikan hanya kepada grup eksperimental dan hasilnya disajikan dalam bentuk persentase. Hasil penelitian ini menunjukkan adanya perbedaan yang siknifikan antara skor menulis siswa yang telah diajar menggunakan Project-Based Task dengan mereka yang tidak. Hal ini terbukti dengan adanya t value yang lebih tinggi dibanding dengan t table (tvalue > ttable)). T value sebesar 2,565 dan t table dengan df 60 (yang terdekat dengan 57) adalah 2,000. Hasil dari motivation test menunjukkan bahwa sebagian besar siswa memiliki motivasi yang lebih besar untuk menulis setelah treatment diberikan. Dengan demikian, dapat disimpulkan bahwa Project-Based Task efektif untuk meningkatkan kemampuan menulis siswa kelas sebelas sekaligus meningkatkan motivasi mereka untuk menulis. Kata Kunci: Kemampuan menulis, Project-Based Task, motivasi.